Characteristics of steel slag as an oxygen carrier for chemical looping gasification of sewage sludge. (15th May 2022) - Zhang, Zhiyuan; Wang, Xutao; Zhang, Lilin; Zhou, Hengtao; Ju, Rui; Rao, Peijun; Guo, Xiaoyu; Han, Yaqian; Chen, Hongwei
Abstract: A comprehensive study was conducted to assess the characteristics of basic oxygen furnace slag (BOFS) and electric arc furnace slag (EAFS) as oxygen carriers for chemical looping gasification (CLG) of sewage sludge (SS). The surface roughness and wear resistance of BOFS were found to be higher than those of EAFS. Further, the oxygen transport capacity of BOFS was higher than that of EAFS at 800 ° C and 900 ° C with the same redox cycles. As the mass ratio increased, the carbon conversion rate and CO2 concentration gradually increased, while the water conversion rate, cold gas efficiency, and H2 and CO concentrations initially increased and then decreased. Both BOFS and EAFS as oxygen carriers had the highest carbon conversion rate and cold gas efficiency when the steam flow rate was 0.15 g min −1 . The cyclic reactivity of BOFS as an oxygen carrier in the CLG process decreased faster than that of EAFS. However, the content of combustible components of BOFS as an oxygen carrier was significantly higher than that of EAFS in each cycle. Overall, these results provide a theoretical basis for steel slag as an oxygen carrier for the CLG of SS. Highlights: Steel slag was used as oxygen carrier for chemical looping gasification of sludge. Basic oxygen furnace slag and electric arc furnace slag were selected for study. Basic oxygen furnace slag has higher surface roughness and wear resistance. Basic oxygen furnace slag as oxygen carrier produced more combustible components. Basic oxygen furnace slag is more suitable as oxygen carrier.